Public Information Disclosure Practice At The Local Government (Case Study Of Magelang And Semarang Cities, Central Java, Indonesia) - Putu Henny Puspawati, Desak (JPAS (Journal of Public Administration Studies), 2016)
This study aims to describe and analyze the implementation of the public information disclosure (PID) practices at the local governmental level. It was carried out in two municipalities in Central Java Province, namely, Magelang and Semarang Cities. The results of the study found many different outcomes in practicing PID in both cities. Compared to Semarang City, Magelang City is still lagging in infrastructure, system of technology and readiness of human resources in the area of information disclosure. The study revealed that PID tends to influence the commitment of local government official to be transparent, as the authority holder in providing information. In the Semarang City case, the local leader and his public officials are seriously handling this policy. The strong willingness of the local leader leads to implement of the regulation, establish proper infrastructure and provide skilled officers. As the result, local government administration is likely to be more accountable, transparent and thereby achieved higher public trust. The lesson learned is the more willing local leaders implement public information disclosure, the more accountable the local government becomes.